2012
DOI: 10.1149/2.053207jes
|View full text |Cite
|
Sign up to set email alerts
|

Multi Length Scale Microstructural Investigations of a Commercially Available Li-Ion Battery Electrode

Abstract: Here we present detailed microstructural investigations of a commercially available Li-ion battery cathode. Without a priori knowledge of the cathode material, we have conducted a thorough multi-modal analysis of the battery electrode using XRD, multi-length scale X-ray microscopy (XRM) and electron microscopy. Multiple length scale X-ray microscopy experiments reveal a wealth of microstructural information in three dimensions including phase fractions, volume specific surface area and tortuosity. At the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 36 publications
3
111
0
Order By: Relevance
“…This way, lower tortuosity values are obtained. 102 This finding is comparable to the analogy by Mandelbrot 149 who stated that the length of a coastline is depending on the resolution of the map. Moreover, the size of the sample volume has to be sufficiently large so that extracted values are representative of the sample bulk.…”
Section: Mesh Based Calculation Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…This way, lower tortuosity values are obtained. 102 This finding is comparable to the analogy by Mandelbrot 149 who stated that the length of a coastline is depending on the resolution of the map. Moreover, the size of the sample volume has to be sufficiently large so that extracted values are representative of the sample bulk.…”
Section: Mesh Based Calculation Methodssupporting
confidence: 77%
“…(19), where Jeff is the effective diffusion flux, c is the molar concentration, ̇ is the effective heat flux, λ bulk is the bulk thermal conductivity. 84,102,146,147 By rearranging the temperature gradient, the heat flux and thus, the tortuosity can be calculated along each axis of a sample. Cooper et al 62 scanned a commercially available LiFePO4 battery cathode using X-ray synchrotron nano CT and investigated the tortuosity of the pore phase using heat flux simulation.…”
Section: Mesh Based Calculation Methodsmentioning
confidence: 99%
“…2) The MATLAB application TauFactor uses an iterative over-relaxation method to solve the diffusion equation and, again, compares the flux through the porous phase to the flux through the dense volume of equal dimensions Brown et al, 2016b;Finegan et al, 2016). 3) The pore centroid method calculates the path length through a porous structure by following the centre of mass of pores of each 2D image slice along the in-plane direction of the volume and dividing it by the thickness of the volume (Gostovic et al, 2007;Smith et al, 2009;Shearing et al, 2012;Cooper et al, 2013;Cooper et al, 2014). 4) The fast marching method calculates the shortest path through the analysed phase by creating a distance map between the starting and end boundary of a propagating front.…”
Section: Image-based Tortuosity Calculation Approachesmentioning
confidence: 99%
“…This highlights the complex interplay between microstructural parameters which is sometimes counter-intuitive where high porosity does not automatically guarantee a low tortuosity (Shearing et al, 2010). Indeed, anisotropies in tortuosity have been found in other porous microstructures featuring even higher porosity (Shearing et al, 2012;Cooper et al, 2014;Tariq et al, 2014).…”
Section: Image-based Tortuosity Calculation Approachesmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35][36] Especially synchrotron X-ray tomography has enabled researchers to obtain unprecedented insights into LIBs from the level of individual particles to the scale of entire electrodes. [37][38][39][40] Most recently, Ebner et al, have directly observed and quantified electrochemical and mechanical degradation in a SnO anode. 41 Using a non-destructive 3D X-ray imagining technique, herein we investigate in 3Ds the gas evolution scenario in a LIB based on a silicon (Si) electrode since Si is considered one of the most promising anode materials for next-generation power sources.…”
Section: Introductionmentioning
confidence: 99%